416 DESMOPLAKIN CARDIOMYOPATHY PRESENTING WITH CARDIAC ARREST IN A PATIENT WITH MYOCARDIAL NON-COMPACTION AND LEFT ACCESSORY PATHWAY. (15th December 2022) - Ragnatela, Ilaria; Santoro, Francesco; Vitale, Enrica; Cetera, Rosa; Santacroce, Rosa; Margaglione, Maurizio; Brunetti, Natale Daniele
Abstract: Introduction: Desmoplakin is a human protein which plays a key role into desmosomes structure. Desmoplakin gene mutations can cause the so-called "desmoplakin cardiomyopathy", a form of arrhythmogenic cardiomyopathy. Its clinical history is characterized by severe ventricular arrhythmias, episodic myocardial injury and left ventricular systolic dysfunction associated with fibrosis. Case Presentation: A 12-years-old male came to our inherited cardiomyopathy ambulatory for cardiological evaluation due to a previous history of cardiac arrest when he was infant (30 days newborn) and palpitation. Previous medical history included eczematous dermatitis and occasional hyperglycemia. During cardiological evaluation EKG was unremarkable, echocardiography revealed myocardial noncompaction in apical and mid-ventricular regions of the left ventricle's infero-lateral wall (end systolic ratio 2:1) and evidence of direct blood flow into deep intertrabecular recesses by colour doppler. Due to history of palpitation an EP study was performed that showed a lateral left-sided accessory pathway that was ablated during the same procedure. A genetic molecular analysis with exome sequencing (NGS, next generation sequencing) was performed and revealed a heterozygous genetic variant in DSP (Desmoplakin) gene on chromosome 6 (c.4046 G>A pSer1349Asn). Familiar screening revealed the same genetic variant in his father and his brother, both had no cardiological events. Conclusion: Desmoplakin cardiomyopathy may have a severe clinical presentation with cardiac arrest. A multidisciplinary approach is suggested for a tailored management of these patients.